TRANSACTIONS IN THE INSURANCE INDUSTRY: A ROAD-MAP - Abdalyan, Ani M. (Assurances)

(untitled) (HEC Montréal, 1998)
The purpose of this article is to provide a road-map to mergers and acquisitions in the insurance industry. The author will set out the ins-and-outs of the documentation of a transaction. Where appropriate, she will sketch some business opportunities and concerns tied in to drafting of the documentation. Finally, she will offer some concluding thoughts on post-mergers management of integration.